Effect of Plasmonic Nanostructures on the Optical Properties of CH3NH3PbI Perovskite Films - Afanasyev, Dmitriy; Ibrayev, Niyazbek; Nuraje, Nurxat (Frontiers in Materials, 2021)
This paper investigated the optical properties of both silver island films (SIF) and CH3NH3PbI3 perovskite films obtained on the surface of SIF. It was found that the surface morphology of SIF has a substantial effect on the optical density of perovskite films. Furthermore, a significant redshift in the absorption spectrum of the island films was observed when perovskite is deposited on them. The intensity and lifetime of the luminescence of perovskite films on the surface of the island films depend on the wavelength of the exciting light. The results indicate that SIFs not only can be potentially used to increase the intensity of light emitting diodes based on perovskites, but also prolong the lifetime of charge carriers in perovskites, and thus lead to potentially improve the photovoltaic properties of perovskite solar cells.